Langerhan′s cell histiocytosis: A single institutional experience - Singh Tejinder; Satheesh C; Appaji L; Aruna Kumari B; Mamatha H; Giri G; Rao Clementina (Indian Journal of Medical and Paediatric Oncology)
Background: Langerhans cell histiocytosis (LCH) is a disease that primarily affects bone but can be associated with a clinical spectrum that ranges from a solitary bone lesion with a favorable natural history to a multisystem, life-threatening disease process. Aim: We analyzed our single institutional experience of managing children with LCH. Settings and Design: A total of 40 children of LCH, managed in tertiary cancer center in South India in the period from 2001 to 2005, were evaluated retrospectively. Materials and Methods: Clinicopathological features, laboratory findings, treatment modalities and long-term outcome were analyzed. Results: Children were aged between 2 months and 12 years, with a mean of 3 years. Majority of the children were below 5 years of age. Group B constituted a bulk of children. Disseminated cases were less (five patients). Liver function dysfunction was seen in four (10%) children. Pulmonary interstitial infiltrates were seen in two (5%) cases. Diabetes insipidus manifested in three patients. There was one death. Conclusion: A better understanding of the etiology and pathogenesis of LCH will result in more directed and efficacious treatment regimens.